MUSLIM PERSONAL LAW AND THE CONSTITUTION OF INDIA: WOMEN’s RIGHTS PERSPECTIVEs - Islam, Mofidul (International Journal of Psychosocial Rehabilitation, 2020)
The right of Muslim women granted by personal law in India is one of the most controversial issues within the framework of human rights. While Indian Constitution formal guarantees to protect the religious rights of members of Muslim communities, whereas the equality rights of Muslim woman have been neglected due to the continuance of personal law system which is discriminatory on the basis of religion and gender. Although Indian government has enacted several laws to protect their rights, granted by the Shariat (Islamic law), towards the provisions of marriage, divorce, and maintenance, but at the level of the society or the community, these provisions have violated due to socio-cultural reasons and the patriarchal legal system which is against the spirit of Indian Constitution. This led to gross violation of their rights granted by Muslim Personal Law towards the provisions of marriage, divorce, and maintenance as well as under the Constitution of India. This paper examines the question of whether the rights granted to Muslim women by personal law based on the Shariat (Islamic law) with regard to marriage, divorce, and maintenance really benefit Muslim women in the society, addressing the issues of gender discrimination and its constitutional validity.